Characterization of n-alkanethiol self-assembled monolayers on mercury by impedance spectroscopy and potentiometric measurements. - Cohen-Atiya, Meirav; Nelson, Andrew; Mandler, Daniel. (J. Electroanal. Chem.Journal of Electroanalytical Chemistry, 2006)
Long chain n-alkanethiol self-assembled monolayers (SAMs) on a hanging Hg drop electrode were studied in detail for the 1st time by impedance spectroscopy (IS) and potentiometry. IS reveals the detailed behavior of the monolayers in the absence and presence of 2 1-electron redox couple: hexaammineruthenium(III) (Ru(NH3)63+) and tris(2,2’-bipyridine)cobalt(III) (Co(bpy)33+). The pinholes-free layers behave as almost ideal capacitors and are permeable to some extent to redox species, depending on their hydrophobicity. Co(bpy)33+ that exhibits sluggish kinetics on a bare Hg electrode reveals a more facile kinetics than Ru(NH3)63+ on an n-octadecanethiol/Hg interface. Potentiometric measurements recorded upon immersing the bare and SAM modified Hg electrode into a soln. contg. a mixt. of the oxidized and reduced forms of the redox couples provide invaluable information on the charge transfer across the monolayer and its ohmic resistance. While Ru(NH3)63+ cannot freely penetrate into the monolayer and therefore establishes a p.d. across the monolayer; penetration of Co(bpy)32+ into the film causes the Fermi level of the Hg surface to attain the Nernst potential of the soln. Finally, increasing the length of the alkane chain of the thiols increases linearly the ohmic resistance of the layer. [on SciFinder(R)]
CAPLUS AN 2006:696886(Journal)
Keywords: alkanethiol self assembled monolayer mercury impedance spectroscopy; cobalt bipyridine complex electrochem redox reaction alkanethiol SAM mercury; ruthenium ammine complex electrochem redox reaction alkanethiol SAM mercury